Pengetahuan, sikap dan ketrampilan penjamah makanan yang diberi pelatihan keamanan pangan di Instalasi Gizi RS Jantung Harapan Kita - Ani Prasetyaningsih; Toto Sudargo; Joko Susilo (Jurnal Gizi Klinik Indonesia, 2005)
Background: Food poisoning occurrence in Indonesia is increasingly growing. Studies also show that nosocomial infection of digestive tract happens in some hospitals because of bacteria transmission. Lack of knowledge, attitude and skills of food handlers about food safety will lead to high risk of disease occurrence cause by food. To prevent such on occurrence, training on food safety for food handlers at hospitals should be held.Objective: To know knowledge, attitude, and practice of food handlers trained on food safety at nutrition installation of Harapan Kita Heart Cardiovascular Hospital..Methods: The study was a quasi-experiment which used pre test-posttest times series design. Subject of the study were 40 food handlers out of 73 total population. Each subject was trained on food safety and observed 3 times (prior to training, 1 month and 2 months after training). Data were analyzed using SPSS for windows version 10.0.Results: After training on food safety given for 5 days there was significant increase of knowledge, attitude and skill of food handlers with p=0.00 (p<0.05) at the period before up to 1 month after training and at the period before up to 2 months after training, but at the period of 1 month up to 2 months there was significant decrease with p=0.00 (p<0.05). Respondent characteristics consisting of age education and length of work did not have significant relationship (p>0.05) with knowledge, attitude and skills of food handlers.Conclusion: There was increase of knowledge, attitude and skill of food handlers before and after 1 month of training.